Magnetic ion oxidation state dependent magnetoelectric coupling strength in Fe doped BCT ceramics. Issue 35 (4th June 2020) - Chawla, Aanchal; Singh, Anupinder; Babu, P. D.; Singh, Mandeep
Abstract : Polycrystalline samples of Ba0.96 Ca0.04 Ti0.91 Fe0.09 O3 were prepared using a conventional solid state reaction route with different Fe starting precursors (Fe2 O3, Fe3 O4 ). A significant difference in the magnetic and ferroelectric properties was observed. Abstract : Polycrystalline samples of Ba0.96 Ca0.04 Ti0.91 Fe0.09 O3 were prepared using a conventional solid state reaction route with different Fe starting precursors (Fe2 O3, Fe3 O4 ). The Rietveld refined XRD data confirmed the phase purity and tetragonal crystal structure of both the samples. The average grain size measured using SEM was ≈0.40 μm in both the samples. XPS analysis confirmed the presence of only Fe 2+ and both Fe 2+ /Fe 3+ in Fe2 O3 and Fe3 O4 doped BCT samples. The P r and M r values have been measured to be 1.34 μC cm −2, 2.88 μC cm −2 and 0.0015 emu g −1 and 0.135 emu g −1 in Fe2 O3 and Fe3 O4 doped BCT samples, respectively. The Fe3 O4 doped samples exhibit much better M-E coupling (≈22%) as compared to Fe2 O3 (≈7%) doped BCT samples. The results obtained hence suggest that Fe3 O4 doping in BCT is better suited for multiferroic applications.